PENGARUH AKTIVITAS SOSIAL MEDIA MARKETING TERHADAP NIAT BELI: PERAN MEDIASI KESADARAN MEREK DI KALANGAN KONSUMEN INDONESIA - Basori, Mohamat; Nugroho, Arif; Hidayat, Arif (Jurnal Keuangan dan Bisnis, 2026)
Purpose: This study aims to examine the effects of social media marketing activities, namely entertainment, personalization, and trendiness, on purchase intention, with brand awareness positioned as a mediating variable within the Indonesian market context. Design Methodology Approach: A quantitative research design was employed using a survey method. Data were collected from respondents in Indonesia who actively engage with social media and have prior experience in online purchasing. Measurement items were assessed using a Likert scale. The proposed model was analyzed using Covariance Based Structural Equation Modeling with LISREL to evaluate both measurement and structural models. Findings: The findings indicate that entertainment exerts a significant positive effect on purchase intention, whereas personalization and trendiness do not demonstrate direct effects. However, all dimensions of social media marketing activities significantly enhance brand awareness. Furthermore, brand awareness is found to fully mediate the relationship between trendiness and purchase intention, while no mediating effect is observed for entertainment and personalization. Practical Implications: The results suggest that marketing strategies should prioritize the development of engaging and trend oriented content to strengthen brand awareness, which subsequently drives purchase intention. The absence of a direct effect of personalization indicates a potential misalignment between current personalization practices and consumer expectations, thereby requiring a more context sensitive and culturally adaptive approach. Originality Value: This study contributes to the literature by providing empirical evidence on the mediating role of brand awareness in the relationship between social media marketing activities and brand awareness in an emerging market setting. The use of a covariance based structural modeling approach strengthens the robustness of model validation and extends methodological rigor in this research stream.